Deskripsi Kemampuan Kognitif Anak Usia Dini Dalam Kegiatan Bermain Lego di TK Kartini - Luly, Julia; Arifin, Irvin Novita; Jamin, Nunung Suryana (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
The purpose of this study is to find out the description of early childhood cognitive abilities in playing lego activities at Kartini Kindergarten, Mopusi Village, Lolayan District, Bolaang Mongondow Regency. The research method used in this study is a qualitative descriptive research method. Data collection techniques used in this study were observation, interviews, and documentation. The number of children who were sampled in this study were 15 children. The results of this study indicate that in the four aspects observed memory, concentration, vocabulary and sharp reasoning are at a good level. Activities that children show such as being able to solve problems when playing lego and can interact using the right vocabulary.